Use of cutting-edge biomedical devices for intravenous cannulation in the health care of a patient: literature review - Zvonka Fekonja; Majda Pajnkihar (Nurses and Midwives Association of Slovenia, 2017)
Introduction: Biomedical devices are tools used for locating invisible and impalpable peripheral veins. The purpose of this article is to give a systematic review and analysis of existing studies on the available biomedical devices used for locating peripheral veins and on their effectiveness in clinical practice. Methods: Databases CINAHL, Medline and ScienceDirect were used for the literature review and analysis. The search was performed with the following key words in English: devices, visualization, technology, cannulation, vein, nursing care, with Boolean operators 'AND' and 'OR'. The analysis included randomized and experimental clinical studies published in the English language in the period from 2000 to August 2016. From a total of 1,020 retrieved studies, 17 were included in the detailed analysis. Results: The results of the analysis have shown that the success rate of the first attempt of intravenous cannulation using biomedical devices in more than half of the studies was not significantly higher than when the process was performed using the conventional method. The success of the first attempt of intravenous cannulation mostly depends on the experience and skills of nurses. Biomedical devices are more helpful for novice nurses who do not perform cannulation on a daily basis, for beginners and nursing students. Discussion and conclusions: Based on research, we cannot affirm that biomedical devices significantly contribute to easier peripheral venous cannulation. Further research is required to validate the advantages of such an approach. However, this is limited due to the affordability issues of such biomedical devices.